Solve for y : 2x - 3y = 12

1 answer

To solve for \( y \) in the equation \( 2x - 3y = 12 \), follow these steps:

  1. Start with the original equation: \[ 2x - 3y = 12 \]

  2. Isolate the term containing \( y \) by subtracting \( 2x \) from both sides: \[ -3y = 12 - 2x \]

  3. Next, divide both sides by \(-3\) to solve for \( y \): \[ y = \frac{12 - 2x}{-3} \]

  4. This simplifies to: \[ y = -\frac{12}{3} + \frac{2x}{3} \] \[ y = -4 + \frac{2}{3}x \]

Thus, the solution for \( y \) is: \[ y = \frac{2}{3}x - 4 \]